2021
DOI: 10.1111/bdi.13154
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of impaired kidney function in patients with long‐term lithium treatment: A systematic review and meta‐analysis

Abstract: Objectives: Although lithium renal effects have been extensively investigated, prevalence rates of chronic kidney disease (CKD) in lithium-treated patients vary. Our aim was to provide prevalence estimates and related moderators. Methods:We performed a systematic review in PubMed/Embase until November 01, 2021, conducting a random effects meta-analysis of studies evaluating CKD prevalence rates in lithium-treated patients calculating overall prevalence ±95% confidence intervals (CIs). Meta-regression analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 65 publications
3
40
1
Order By: Relevance
“…Considering the above findings, not only lithium treatment duration, 3,4 but also type-2 diabetes mellitus, 2 benzodiazepine use, 2 cardiovascular disease, 3 albuminuria, 4 hypertension, 4 hypothyroidism, 4 and microcysts 4 may possibly worsen renal function independently or moderate the risk of impaired renal function induced by lithium. In addition, the debate on the role of episodes of acute lithium toxicity as risk moderators is ongoing.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Considering the above findings, not only lithium treatment duration, 3,4 but also type-2 diabetes mellitus, 2 benzodiazepine use, 2 cardiovascular disease, 3 albuminuria, 4 hypertension, 4 hypothyroidism, 4 and microcysts 4 may possibly worsen renal function independently or moderate the risk of impaired renal function induced by lithium. In addition, the debate on the role of episodes of acute lithium toxicity as risk moderators is ongoing.…”
mentioning
confidence: 91%
“…In addition, the debate on the role of episodes of acute lithium toxicity as risk moderators is ongoing. 3…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium, a well-known mood stabilizer, has long been used to treat mania in patients with bipolar disorder (BP), and as a synergist in the treatment of depression in these patients, especially those who have attempted suicide (1). These applications have been proven to be clinically effective (2)(3)(4)(5), and based on data from many double-blind randomized controlled studies and other research, lithium is the goldstandard maintenance treatment for BP (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). More notably, Rybakowski modified the definition of mood stabilizer: ' A drug that if used as mono-therapy: (1) act therapeutically in mania or/and in depression; (2) acts prophylactically against manic or/and depressive episodes as demonstrated in a trial of at least 1 year's duration and (3) does not worsen any therapeutic or prophylactic aspect of the illness outlined above.'…”
Section: Introductionmentioning
confidence: 99%
“…13 A recent meta-analysis of observational studies has suggested that one fourth of the patients treated with lithium may develop moderate or advanced CKD after longterm treatment, with a two-fold increased risk compared with patients receiving treatments other than lithium. 14 Interestingly, lithium might also have an impact on thyroid and parathyroid function as well, potentially increasing the risk of hypothyroidism and raising total plasma calcium concentration. 11 Using the comprehensive high-quality Danish registers, combining prescription information with laboratory data, we aimed to assess the association between use of lithium and the subsequent risk of CKD.…”
mentioning
confidence: 99%